Overclaim Clarification: The Influence Of Perceived Risk And Online Customer Review On Repurchase Intention Through Brand Trust In The Originote - Livia Deviana; Heriyadi Heriyadi; Bintoro Bagus Purmono; Wenny Pebrianti; Ahmadi Ahmadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The beauty industry in Indonesia has experienced rapid growth, many brands use marketing strategies by highlighting products percentage claims. However, overclaim issues have emerged as experienced by The Originote and caused a shift in brand positioning and trust. In response, The Originote implemented clarification and product reformulation to restore trust and repurchase intention. This study aims to identify factors influencing repurchase intention by using perceived risk, online customer review, and brand trust. The research using Stimulus–Organism–Response Theory. A quantitative approach was employed using a survey method, and data were analyzed using SmartPLS version 4.0. The study involved 200 respondents who were consumers of The Originote. The findings reveal that perceived risk and online customer reviews have a significant influence on brand trust and repurchase intention. Additionally, brand trust has a positive and significant effect on repurchase intention and serves as a mediating variable between the independent variables on repurchase intention. These results highlight the crucial role of perceived risk, online customer reviews, and brand trust in shaping repurchase intention in the beauty industry facing overclaim issues. This study provides practical and theoretical contributions for companies in developing effective marketing strategies and managing long term consumer and brand relationships.